„Wędrujące pojęcia”. Koncepcja Mieke Bal – przykład inter- czy transdyscyplinarności? - Tabaszewska, Justyna (Studia Europaea Gnesnensia, 2013)
The notions of inter- and transdisciplinarity represent categories which the humanities frequently resort to in the discourse, but which remain difficult to define. The attempts to do so are most often associated with subscribing to one of the possible models of interpreting relationships between individual disciplines of science. Mieke Bal’s concept of transdisciplinarity, which this paper discusses, envisages a framework where the privileged form of formulating scientific concepts would be in research practice that is rooted not only in the methodologies of individual sciences but most of all in the everyday practices and experiences.